Food allergen labeling in developing countries: Insights based on current allergen labeling practices in Malawi. (February 2018) - Mfueni, Eston; Gama, Aggrey Pemba; Kabambe, Peter; Chimbaza, Monica; Matita, Grey; Matumba, Limbikani
Abstract: Food allergen labeling is an important tool in minimizing the risk of exposure to foods allergens and the resultant adverse effects for individuals with food allergies. Unlike in the industrialized countries, there have been very few studies that have scrutinized food allergen labels and analyzed the robustness of food allergen regulation in developing countries. In the present study, food allergen labeling of 105 supermarket food products in Malawi were evaluated. Furthermore, Malawi's allergen labeling regulation was compared with Codex general standard on labeling, and regulations in force in the E.U, U.S, and Republic of South Africa. About 54.3% of the surveyed products carried the special allergen declaration in addition to the declaration on the list of ingredients, 23.8% used special emphasis (bolding, italic, contrasting color and enlarged font) when declaring allergens on the ingredient list, and 28.6% used precautionary allergen labeling (PAL). Notably, none of the surveyed locally manufactured products had any of these features. However, all the surveyed products complied with the allergen labeling requirements stipulated in Malawi General Standard for Labeling of Prepacked Foods implying that the Malawi standard is not protective enough. Moreover, Malawi's allergen labeling regulation was found to be the least demanding. Although this study is based on data from Malawi, trends and implications for standards development may be applicable to other developing countries especially those in Sub-Saharan Africa. Highlights: Malawi's food allergen labeling regulation was found to be the least demanding and most relaxed among those scrutinized. All sampled products complied with Malawi's food allergen labeling regulation. No locally manufactured products used special emphasis and/or precautionary allergen labeling.